Pengaruh Disiplin Kerja, Lingkungan Kerja, dan Komitmen Organisasional terhadap Kinerja Karyawan: Studi pada Rumah Sakit Islam Banjarmasin - Burhannudin Burhannudin; Mohammad Zainul; Muhammad Harlie (Universitas Proklamasi 45 Yogyakarta, 2019)
This study aims to examine the effect of work discipline, work environment, and organizational commitment partially or simultaneously on employee performance at the Banjarmasin Islamic Hospital. This research was conducted on non-medical employees of the Banjarmasin Islamic Hospital. There are 55 respondents who have been selected as samples using the Slovin formula. The method used is the survey method, while the type of research is classified as explanatory research. The method of data collection uses a questionnaire with a Likert scale. Data analysis using multiple linear regression, hypothesis testing and coefficient of determination are assisted by IBM Version 24 Statistical Product and Service Solutions (SPSS). The results show: (1) Work discipline has a partial effect on employee performance at Banjarmasin Islamic Hospital; (2) The work environment has a partial effect on employee performance at the Banjarmasin Islamic Hospital; (3) Organizational commitment has a partial effect on employee performance at Banjarmasin Islamic Hospital; (4) Work discipline, work environment and organizational commitment have a simultaneous effect on employee performance at Banjarmasin Islamic Hospital.